Investigation of Asset Securitization in Chinese Commercial Banking Sector and Case Studies between U.S. and China - Gu, Qi (2007)
Abstract This paper provides an investigation of Chinese asset securitization in commercial banking sectors. Asset securitizations as one of the most important methods for capital gather and enhance banking liquidity. From it development in the U.S. ABS market in the 1970's it is now recognised by Chinese financial institutions and Chinese commercial banks are state-owned, which play main role in the asset securitization. The different banking system between U.S. and China, reflect on the management of asset securitization with government support and ABS market. U.S. has mature asset securitization market and successful in types of securitization, and leading world development of asset securitization markets. China began with asset securitization in 2005, up to two years pilot projects implement in commercial banks, these push Chinese whole banking sector in asset securitization improvement. However, China is in the beginning step in asset securitization and in the sprout period of ABS market. Especially with the potential of Chinese mortgage loans and credit cards areas and so on. Those types of asset securitization would be the further perspective in Chinese securitization development direction. Thus, for Chinese immature ABS market and government policy with power controls there need be compared with mature developed ABS in U.S. and further improvement of Chinese asset securitization need to fill the gap of banking system and external aspects to catch up with U.S and maintain Chinese banking sectors stability.